PERCEPTION OF PADDY RICE FARMERS TOWARDS THE USE OF IRRIGATION FACILITIES IN IMPROVING REGIONAL FINANCIAL PERFORMANCE "Case Study of Indonesia and Malaysia" - Leni Handayani; Alistraja Dison Silalahi; Sri Wahyuni; Dian Habibie; Mariam Setapa; Tismazammi Mustafa (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
This study aims to determine the perception of farmers towards the use of irrigation facilities in an effort to increase the income of paddy rice farmers (Case Study: Paddy Rice Farmers in Indonesia and Malaysia. The method used with the Likert scale is a scale used to measure, behavior, attitude or opinion of a person or group regarding a social event or phenomenon. The results of the study show that the perception of paddy rice farmers towards the use of irrigation facilities in Indonesia, that the highest Score Index is found in the use of fertilizer (98%). With the use of irrigation facilities, it is more economical to use fertilizers. The respondents' answers were 9 (30%) farmers who stated that they strongly agreed, 12 (40%) stated that Sutuju and 9 (30%) stated that they were Neutral and the lowest score index was in the use of pesticides (75%). The use of irrigation facilities can reduce the use of pesticides. The respondents' answers were 5 (16.7%) farmers who stated that they strongly agreed, 15 (50%) stated that Sutuju and 10 (33.3%) stated that they were neutral. The perception of paddy rice farmers towards the use of irrigation facilities in Malaysia, that the highest Score Index is found in the land area (98%). The more land planted with rice paddies using irrigation facilities, the higher the production. The respondents' answers were 28 (93.3%) farmers who stated that they strongly agreed, 2 (6.67%) stated that they agreed and it was easier to manage land that uses irrigation facilities. The respondents' answers were 26 (86.6%) farmers who stated Strongly Agree, 4 (13.3%) stated Sutuju, so with the hope that all rice farmers want irrigation and the lowest score index is in the use of pesticides (78%).